Kajian Yuridis Penyelesaian Perselisihan Hasil Pemilihan Kepala Desa - Supriyadi Supriyadi (Jurnal Cakrawala Hukum, 2019)
Headman election are part of a village government implementation system that transparent, independent, accountable and democratic. Conducting headman election in direct, general, free, confidental, honest and fair are expected to produce a headman who is able to lead and organize village government in effective, efficient, responsible manner, and trusted by the villagers. This kind of headman can create and increase the welfare of the villagers. Based on juridical study, the legislation that directly regulates headman election is not adequate enough for the provision concerning dispute of headman election result. It only appoint regent/mayor as a party that obligated to settle disputes within 30 (thirty) days, and a deadline to submit an objection is 3 (three) days. Therefore, making a more technical regulationregarding the stages, mechanisms, and procedures for resolving headman election disputes in a form of regional legal products will greatly help providing a solution for the election implementation committee at both the village and regency/city level, candidates for headman, villagers, and regent/mayor who was given the obligation to resolve dispute of headman election result.How to cite item: Supriyadi, S. (2019). Kajian Yuridis Penyelesaian Perselisihan Hasil Pemilihan Kepala Desa. Jurnal Cakrawala Hukum, 10(2), 228-237. doi:https://doi.org/10.26905/idjch.v10i2.3541